Banking Integration in European Context - Roxana Bădîrcea; Alina Manta; Ramona Pîrvu; Nicoleta Florea (Amfiteatru Economic Journal, 2016)
The integration of different states in a already existing union or in a new one represents a long-lasting process involving harmonisations on various fields – political, economic, legislative, social, cultural, technological, informational, etc. Besides the integration of the states and of the different authorities in a common mechanist, the business organizations also have to comply with certain standards and to align to certain procedures. The banking system is not an exception being probably one of the pillars of the economic and financial integration of a state in a union. Banking integration may be considered the process leading to a convergence towards a single market for all products, processes, procedures, standards, transactions from the banking field. All sets of standards, mechanisms and procedures should be observed both by banks, regulation and control bodies, but also by customers. Only in this way one can create the premises for the most favourable banking transactions. The integration of the banking system in a union is determined, conditioned and influenced by a series of factors. Based on the data published by the Bank for International Settlements, the authors carry out a close and pertinent empirical analysis of the banking assets flows between the Eurozone countries in the period 2000-2014. The paper also deals with the commitments that the recent economic-financial crisis created on the banking assets flows. The authors resort to regression equations in order to demonstrate the connection between the effects of banking integration and various factors involved (the relative dimension of the country, the significance of the banks in the financial system, the Herfindhal index, the degree of concentration or dispersion of the property on banks, the degree of independence, the tradition of law). In order to measure the level of banking integration of the national bank systems, the indices we used are the degree of openness towards the exterior, the degree of internationalization of the national bank systems in the Eurozone. The results of this research point out a whole series of commitments from a scientific point of view, but also regarding a good practices model which should enhance the synergic integration of the different national banking systems. A part of the outlined conclusions may be oriented towards specific directions and levers in order to modify the national strategyfor the adaptation of a candidate state to the Aquis communautaire.
Keywords: F36; G21; G01; 330; banking integration; banking assets flows; degree of openness of the banking systems towards the exterior; degree of internationalisation of the banking systems